Experimental investigation of air velocity, water flow rate, and staging of cooling pad on the performance of direct evaporative coolers - Tazebew Dires Kassie; Yaregal Eneyew Bizuneh; Amare Merfo Amsal (International Journal of Air-Conditioning and Refrigeration)
Abstract In hot and dry climates, improving air cooling efficiency is vital for reducing energy consumption and enhancing indoor comfort. An evaporative cooling system utilizes water evaporation to cool air effectively. This study experimentally analyzes a direct evaporative cooler (DEC) set in a controlled environment to optimize key performance parameters, including air velocity, water consumption rate, cooling pad staging, humidity levels, and cooling capacity. Results indicated that a maximum cooling capacity of 17.6 W/m2 was achieved at 6.8 °C dry bulb temperature drop and a 33.5% rise in relative humidity across the cooling chamber. A strong linear relationship was observed between air velocities and cooling capacity, increasing by 4.43 W/m2 for every 1 m/s rise in airflow. Additionally, a three-stage cooling pad configuration outperformed single and two-stage setups, achieving the highest system effectiveness of 65% alongside a 32.8% rise in humidity. These findings highlight the potential of multistage DEC systems with natural cooling pads for energy-efficient climate control solutions.